2017
DOI: 10.1089/met.2017.0095
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl Peptidase-4 Inhibitor Sitagliptin Prevented Weight Regain in Obese Women with Polycystic Ovary Syndrome Previously Treated with Liraglutide: A Pilot Randomized Study

Abstract: Sitagliptin in adjunct to metformin prevented weight regain in obese women with PCOS previously treated with liraglutide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 28 publications
0
40
0
Order By: Relevance
“…Other side effects such as edema [21] and bone fractures [22] were also related to the use of pioglitazone. In a previous study, TECOS in adjunct to DMBG prevented weight regain more effectively than DMBG alone in obese women with PCOS previously treated with liraglutide [6]. Another study also showed that TECOS improved beta-cell function and prevented a conversion to impaired glucose tolerance and type 2 diabetes in DMBG-intolerant and obese PCOS patients [23].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Other side effects such as edema [21] and bone fractures [22] were also related to the use of pioglitazone. In a previous study, TECOS in adjunct to DMBG prevented weight regain more effectively than DMBG alone in obese women with PCOS previously treated with liraglutide [6]. Another study also showed that TECOS improved beta-cell function and prevented a conversion to impaired glucose tolerance and type 2 diabetes in DMBG-intolerant and obese PCOS patients [23].…”
Section: Discussionmentioning
confidence: 94%
“…Sitagliptin (TECOS) was the first DPP-4 inhibitor approved by the FDA for the treatment of type 2 diabetes. It has been previously observed that TECOS in adjunct to DMBG prevented weight regain more effectively than DMBG alone in obese women with PCOS previously treated with liraglutide [6]. However, the efficacy and potential mechanism of the combination therapy with DMBG and TECOS in PCOS remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…similarly found that sitagliptin prevents weight regain, as compared to metformin alone, in a 12-week prospective open label study in 24 obese women with PCOS previously treated with liraglutide. (47) Thus, a growing body of evidence suggests that sitagliptin selectively reduces VAT. Despite the improvements in VAT and GH secretion, we did not observe an improvement in any of the clinical signs or symptoms experienced by women with PCOS, as reported in a validated PCOS questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Ferjan et al showed in a pilot randomized study that sitagliptin may prevent weight regain in metformin intolerant obese women with PCOS [162]. The same authors reported that sitagliptin in combination with metformin prevented weight regain more effectively than metformin [163]. Therefore, further studies are warranted to prove a possible therapeutic benefit and advantage of these newer groups of hypoglycemic agents over metformin in the management of PCOS.…”
Section: Polycystic Ovary Syndrome (Pcos)mentioning
confidence: 99%